Leverage and Bubbles: Experimental Evidence - Paul Gortner; Baptiste Massenot (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2020)
We investigate the effect of leverage on bubbles in an asset market experiment. We expect higher leverage to produce larger bubbles because (i) it creates moral hazard in a setup with limited liability and (ii) it increases aggregate liquidity. Inconsistent with the moral hazard channel, which we test by holding aggregate liquidity constant, higher leverage does not produce larger bubbles. To understand this unexpected result, we run the same experiment with a different framing: instead of repaying debt, participants can earn a bonus. This bonus treatment produces larger bubbles, suggesting that more leveraged participants trade more cautiously to avoid default. Finally, bubbles are larger and increase over time when we keep leverage constant over time by injecting liquidity in the economy. Overall, these results suggest that higher leverage inflates bubbles not because of moral hazard but because of more abundant liquidity.
Keywords: G28; E58; 330